دور علم النفس اللغوي في تدريس اللغة العربية - Mohammed Muhsin El Thaqefi (UIN Fatmawati Sukarno Bengkulu, 2018)
AbstractThis research revolves around the role of linguistic psychology in the teaching of the Arabic language The Arabic language is the key to Islamic culture, and the Muslim individual will not be able to establish a true Islamic culture unless the Arab is able to shape his consciousness and his motives and behaviors. These studies are mainly to serve Islam and to understand the Holy Quran and the Hadith and the psychological in human. In this research, many studies were conducted on the role of language psychology in teaching Arabic to Indonesian students in general and to students of the State Institute for Islamic Studies, Bengkulu in particular. This research follows the descriptive approach as the appropriate method for the nature of research. Key word: Language psychology; Teaching Arabic;